Addressing Goal Conflicts: New Policy Mixes for Commercial Land Use Management. - (:unkn) unknown (MDPI, 2022)
Commercial land use management that focuses on a future-oriented urban and regional development must address multiple goals. Effective policy mixes need to simultaneously (1) improve city-regional and inter-municipal cooperation, (2) reduce land take, and (3) assure the long-term economic development of a region. Using the Northern Black Forest in Germany as a case study, we brought together planning and land use research with public policy analysis. We applied crossimpact balances (CIB) to build and analyze a participatory policy-interaction model. Together with a group of 12 experts, we selected effective individual measures to reach each of the three goals and analyzed their interactions. We then assessed the current policy mix and designed alternative policy mixes. The results demonstrate that current approaches to commercial land use management present internal contradictions and generate only little synergies. Implementing innovative measures on a stand-alone basis runs the risk of not being sufficiently effective. In particular, the current practice of competing for municipal marketing and planning of commercial sites has inhibiting effects. We identified alternative policy mixes that achieve all three goals, avoid trade-offs, and generate significant synergy effects. Our results point towards a more coherent and sustainable city-regional (commercial) land-use governance.
Keywords: Schwarzwald; Regionalentwicklung; Stadtentwicklung; Gewerbefläche; Interkommunale Zusammenarbeit; Flächeneinsparung; Regionalwirtschaft; Nachhaltige Entwicklung; Flächennutzungsplanung; Flächenmanagement